2013
DOI: 10.1111/pde.12207
|View full text |Cite
|
Sign up to set email alerts
|

Polyarteritis Nodosa in Childhood: Recognition of Early Dermatologic Signs May Prevent Morbidity

Abstract: Systemic polyarteritis nodosa (PAN) is a vasculitis that affects small to medium-size arteries. Onset in childhood is rare and can cause significant morbidity. Often, cutaneous manifestations can provide early clues toward diagnosis. This article describes a case of childhood systemic PAN that presented with fever, a necrotic skin lesion, and oral ulceration. Intestinal perforation complicated this case. Prompt recognition of childhood PAN is important to prevent serious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In children, Ozen et al reported gastrointestinal symptoms in 24% of 63 children with PAN [ 6 ]. Another study evaluated the cardiac findings of 15 children with childhood PAN [ 2 ]. The most common findings were diminished left ventricular systolic function and mild mitral and/or tricuspid valve regurgitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children, Ozen et al reported gastrointestinal symptoms in 24% of 63 children with PAN [ 6 ]. Another study evaluated the cardiac findings of 15 children with childhood PAN [ 2 ]. The most common findings were diminished left ventricular systolic function and mild mitral and/or tricuspid valve regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical spectrum is highly variable where it can be systemic or localized to one organ or system [ 1 ]. PAN occurs primarily in middle-aged adults but appears even more rarely in children where both girls and boys are affected equally [ 2 ]. It occurs in different forms as cutaneous (the most common form), classic, systemic, or microscopic.…”
Section: Introductionmentioning
confidence: 99%
“…PAN with ruptured aneurysms is a rare but life-threatening condition in children. Several studies have revealed high mortality rates of PAN in children who presented with acute abdomen despite the administration of combined medical and surgical treatment 7,8. Approximately 50% of the patients with systemic PAN have GI involvement ranging from mild to severe manifestations 1.…”
Section: Discussionmentioning
confidence: 99%
“…Criteria for diagnosing childhood PAN were published recently by the European League Against Rheumatism/Paediatric Rheumatology International Trials Organisation/Paediatric Rheumatology European Society (see table 1). 5 9…”
Section: Discussionmentioning
confidence: 99%